The Process of Teaching and Learning English Used by teacher at SMPN 1 Poso Pesisir Utara - Mamudi, Sitti Fitriawti; Poima, Adrian (Sintuwu Maroso Journal of English Teaching, 2024)
The objective of this research was to describe the process of the teaching and learning Englishused by teacher at SMP Negeri 1 Poso Pesisir Utara in Academic year 2022/2023. I this study the researchers using a qualitative approach to the type of descriptive study. the researcher collected the data from English teachers in SMP Negeri 1 Poso Pesisir Utara that have been using the curriculum 2013 in the process of learning. The eighth grade of SMP Negeri 1 Poso Pesisir Utara to describe teaching activities that are often used by teachersand the students. The Procedure data collection in this study was used Observation, Interview and Documentation. Data Analyzed was used Miles and Huberman ,theory framework for qualitative data analysis by three components: data reduction, data display, and drawing or verifying conclusion. the results of the English teaching and learning process in the previous chapter, it can be seen that the process of English learning uses steps of the teaching learning process in class include the opening activity, the main activity, and the closing activity. The primary activities are watching, questioning, investigating, accommodating, and communicating.